Circular RNA CircFAM188B Encodes a Protein That Regulates Proliferation and Differentiation of Chicken Skeletal Muscle Satellite Cells - Yin, Huadong; Shen, Xiaoxu; Zhao, Jing; Cao, Xinao; He, Haorong; Han, Shunshun; Chen, Yuqi; Cui, Can; Wei, Yuanhang; Wang, Yan; Li, Diyan; Zhu, Qing (Frontiers in Cell and Developmental Biology, 2020)
Circular RNAs (circRNAs) are recognized as functional non-coding transcripts; however, emerging evidence has revealed that some synthetic circRNAs generate functional peptides or proteins. Additionally, the diverse biological functions of circRNAs include acting as miRNA-binding sponges, RNA-binding protein regulators, and protein translation templates. Previously, we found that circular RNA circFAM188B is a stable circular RNA and differentially expressed between broiler chickens and layers during embryonic skeletal muscle development. In this study, we found that circFAM188B exhibited a unique pattern of sharply decreased expression from embryonic day 10 (E10) to Day 35 (D35) after hatching. Our experimental results showed that circFAM188B promotes the proliferation, but inhibits the differentiation of chicken skeletal muscle satellite cells (SMSCs). Bioinformatic analysis revealed circFAM188B contain an opening reading frame (ORF) which translate into circFAM188B-103aa, internal ribosome entry site (IRES) analysis further confirmed the coding potential of circFAM188B. In addition, western blot assay detected a flag tagged circFAM188B-103aa, and several peptides of circFAM188B-103aa were detected by LC-MS/MS analysis. We further verified that the role of circFAM188B in chicken myogenesis is consistent with that of its parent transcript circFAM188B, and circFAM188B-103aa facilitates chicken SMSC proliferation, but represses differentiation. Taken together, these results suggested that a novel protein circFAM188B-103aa encoded by circFAM188B that promotes the proliferation but inhibits the differentiation of chicken SMSCs.